Histopathological pattern of lymphomas and clinical presentation and outcomes of diffuse large B cell lymphoma: A multicenter registry based study from India - Ramesh B. V. Nimmagadda; Raghunadharao Digumarti; Reena Nair; Dinesh Bhurani; Vinod Raina; Shyam Aggarwal; Shekhar Patil; Pabitra K Gogoi; Subramanian Sundaram; Chanchal Goswami; Shashikant Apte; Srinivas Chakravarthy; et al. (Indian Journal of Medical and Paediatric Oncology)
Context: The distribution of various subtypes of lymphomas in India is different from other parts of the world. There is scarce multicentric data on the pattern and outcomes of lymphomas in India. Aims: The aim of this study is to evaluate the histopathological and the clinical pattern and treatment outcomes of lymphomas in India based on the retrospective data collected from a multicenter registry. Materials and Methods: Retrospective data was collected at 13 public and private hospitals in India for patients diagnosed with lymphoma between January 2005 and December 2009. The data collection was performed in the setting of a multicenter lymphoma registry Survival analyses were performed using the Kaplan-Meier method and compared using the log-rank test. Results: Non-Hodgkin′s lymphoma (NHL) constituted 83.17% and Hodgkin′s lymphoma (HL) for 16.83% of the 1733 registered and analyzed cases. Diffuse large B cell lymphoma (DLBCL) was the most common NHL (55%) followed by follicular lymphoma (11%). CHOP was the most common chemotherapy regimen administered (84%) while rituximab was used in 42.7% of those with DLBCL. Survival analysis of treatment naïve DLBCL patients (n = 791) was performed. Of these, 29% were lost to follow-up, 20% with active disease. The median follow-up in surviving patients is 31 (range: 1-88) months. Median progression-free survival (PFS) and overall survival (OS) in DLBCL patients has not reached. There was no significant difference in median PFS (69 months vs. 61 months, P = 0.1341), but OS was significant not reached (NR) vs. NR, P = 0.0012) within international prognostic index high or intermediate subgroups. Rituximab use was associated with significantly prolonged PFS (NR vs. 82 months, P = 0.0123), but not OS (NR vs. NR, P = 0.2214). Cox regression analysis in treatment naïve DLBCL patients showed a performatnce status, stage and receipt of six or more cycles of chemotherapy to be significantly associated with OS and all of the preceding plus rituximab use significantly associated with PFS. Conclusions: Our analysis confirms previous reports of distribution of lymphoma subtypes in India and suggests that patients who are able to receive the full course of chemotherapy achieve a better outcome. This indicates the importance of ensuring compliance to treatment utilizing various measures including patient and family counseling. Prospective studies are required to confirm these findings.